A Review on Food Supplement-Nutraceuticals - Singh, Jitendra; Ancheria, Rahul Kumar; Khinchi, M. P.; Nama, Nitin; Singh, S. P. (Asian Journal of Pharmaceutical Research and Development, 2017)
Nutraceutical-rich vegetables and fruits are an important module of a healthy diet. It has been shown that people consuming healthy diets, living active lifestyles, not smoking and not indulging in excessive alcohol consumption tend to have a reduced risk of CVD. There has been an detonation of consumer interest in the health enhancing role of physiologically-active specific nutraceuticals. Such products include food supplements, dietary supplements, value-added processed foods as well as non-food supplements such as tablets, soft gels, capsules etc. The explosive growth, research developments, lack of standards, marketing zeal, quality assurance and regulation will play a vital role in its success or failure